2012
DOI: 10.1556/achrom.24.2012.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of Naringenin and kaempferol inMelastoma decemfidumextracts by GC-FID and GC-MS

Abstract: Summary.Melastoma decemfidum is a plant species from the Melastomataceae family. The plant was reported to have bioactive flavonoids, which showed antioxidant and cytotoxic activities. Extracts from the leaves of 26 plants were made at room temperature with methanol. Detection and quantification of two of the flavonoids, namely naringenin and kaempferol, in the extracts were carried out by using gas chromatography-flame ion detection (GC-FID) and gas chromatography-mass spectrometry (GC-MS). By optimizing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…The most prominent product ion at m/z 273 was formed by loss of water and a carbon monoxide group from [M + H] + . The ion at m/z 153 corresponded to the loss of the C 8 H 6 O 4 – group from [M + H] + , consistent with the molecular formula C 7 H 4 O 4 + . In the MS 3 spectrum, the ion at m/z 273 lost a carbon monoxide group to produce the m/z 245 ion, and further loss of a carbon monoxide group produced the m/z 227 ion.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The most prominent product ion at m/z 273 was formed by loss of water and a carbon monoxide group from [M + H] + . The ion at m/z 153 corresponded to the loss of the C 8 H 6 O 4 – group from [M + H] + , consistent with the molecular formula C 7 H 4 O 4 + . In the MS 3 spectrum, the ion at m/z 273 lost a carbon monoxide group to produce the m/z 245 ion, and further loss of a carbon monoxide group produced the m/z 227 ion.…”
Section: Resultsmentioning
confidence: 80%
“…In the experiment, the fragmentation mechanisms of the 29 compounds were analyzed by using electrospray ionization ion trap mass spectrometry (ESI-ITMS) and atmospheric pressure chemical ionization ion trap mass spectrometry (APCI-ITMS) in the multi-stage MS full scan mode. These compounds included streblusol D (1), [3] magonlignan A 4'-O-α-D-glucopyranoside (2), magnolol (3), magnaldehyde D (4), erythro-strebluslignanol (5), threo-strebluslignanoxiranol (6), strebluslignanphenol (7), threo-strebluslignanol A (8), erythro-strebluslignanol B (9), erythrostrebluslignanol C (10), strebluslignanol D (11), strebluslignanone (12), (7'R,8'R,7"R,8"R)-threo-strebluslignanol F (13), (7'R,8'S,7"R,8"S)erythro-strebluslignanol G (14), isomagnaldehyde (15), isostrebluslignaldehyde (16), isomagnolol (17), myricetin (18), naringenin (24), [22][23][24] α-boswellic acid (25), β-boswellic acid (26), oleanolic acid (27), β-amyrin (28) and β-amyrenone (29). Their structures are shown in wileyonlinelibrary.com/journal/rcm Reference compounds 1, 2, 4, 8-11 and 25 were separately injected and detected in the negative ion mode using the ESI source.…”
Section: Resultsmentioning
confidence: 99%
“…GC-FID and quantitative analyses were carried out according to previously published method (Sarju et al 2012). A gas chromatograph (HP-6890N, Agilent, USA) equipped with an HP-5 fused silica capillary column (30.0 m × 0.32 mm i.d., film thickness 0.25 µm) was used.…”
Section: Detection and Quantification Of Flavonoidmentioning
confidence: 99%
“…Several flavonoids have been detected in plant extracts of J. gendarussa using high performance liquid chromatography (HPLC) (Mustafa et al 2010). In addition, a simple and efficient method for detection and quantification of naringenin and kaempferol from fresh crude extracts of Melastoma decemfidum using GC-FID has been reported (Sarju et al 2012). Hence, to the best of our knowledge, this is the first study of the detection and quantification of naringenin and kaempferol from young and mature leaves in J. gendarussa from different locations in southern region of Peninsular Malaysia using The commercial standard of naringenin and kaempferol were purchased from Sigma-Aldrich (Subang Jaya, Selangor, Malaysia).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, plant extracts of M. decemfidum have been used to treat mouth ulcers, toothaches and sinusitis and have been employed as a diuretic (Zakaria & Mohd 1994;Lohezic-Le et al 2002). Several flavonoids, such as rutin, quercitrin, quercetin (Nazlina et al 2008), naringenin and kaempferol, have been identified from M. decemfidum tissue (Susanti et al 2007;Sarju et al 2012). Furthermore, crude flower extracts have demonstrated strong cytotoxic effects in MCF7 (Susanti et al 2007) and HeLa cell lines (Zakaria et al 2011).…”
Section: Introductionmentioning
confidence: 99%